Non-RBM Mutations Impaired SARS-CoV-2 Spike Protein Regulated to the ACE2 Receptor Based on Molecular Dynamic Simulation - Du, Yaoqiang; Wang, Hao; Chen, Linjie; Fang, Quan; Zhang, Biqin; Jiang, Luxi; Wu, Zhaoyu; Yang, Yexiaoqing; Zhou, Ying; Chen, Bingyu; Lyu, Jianxin; Wang, Zhen (Frontiers in Molecular Biosciences, 2021)
The emergence of novel coronavirus mutants is a main factor behind the deterioration of the epidemic situation. Further studies into the pathogenicity of these mutants are thus urgently needed. Binding of the spinous protein receptor binding domain (RBD) of SARS-CoV-2 to the angiotensin-converting enzyme 2 (ACE2) receptor was shown to initiate coronavirus entry into host cells and lead to their infection. The receptor-binding motif (RBM, 438–506) is a region that directly interacts with ACE2 receptor in the RBD and plays a crucial role in determining affinity. To unravel how mutations in the non-RBM regions impact the interaction between RBD and ACE2, we selected three non-RBM mutant systems (N354D, D364Y, and V367F) from the documented clinical cases, and the Q498A mutant system located in the RBM region served as the control. Molecular dynamics simulation was conducted on the mutant systems and the wild-type (WT) system, and verified experiments also performed. Non-RBM mutations have been shown not only to change conformation of the RBM region but also to significantly influence its hydrogen bonding and hydrophobic interactions. In particular, the D364Y and V367F systems showed a higher affinity for ACE2 owing to their electrostatic interactions and polar solvation energy changes. In addition, although the binding free energy at this point increased after the mutation of N354D, the conformation of the random coil (Pro384-Asp389) was looser than that of other systems, and the combined effect weakened the binding free energy between RBD and ACE2. Interestingly, we also found a random coil (Ala475-Gly485). This random coil is very sensitive to mutations, and both types of mutations increase the binding free energy of residues in this region. We found that the binding loop (Tyr495-Tyr505) in the RBD domain strongly binds to Lys353, an important residue of the ACE2 domain previously identified. The binding free energy of the non-RBM mutant group at the binding loop had positive and negative changes, and these changes were more obvious than that of the Q498A system. The results of this study elucidate the effect of non-RBM mutation on ACE2-RBD binding, and provide new insights for SARS-CoV-2 mutation research.